Empowering the people [review of] - Lee, Gloria R. (1996)
A review of Horacio R. Morales, Jr., A call for People's Development, edited by Cesar Cala and Jo Doñgail (National Council of Churches in the Philippines, 1990), 182 pages.
Keywords: Book reviews